(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2022)
This article reflects on the characteristics of laughter obtained in O Cabaré dos Quase-Vivos, a show created more than fifteen years ago by the Grupo Sobrevento de Teatro, which proposes questions that are still relevant today. It is a show that moves between the comic and the dramatic, playing with the spectator’s perception between sad puppet show scenes and relaxed scenes, which casually mix puppets with actors.